2002
DOI: 10.1074/jbc.m103607200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Eukaryotic Initiation Factor 4E Markedly Reduces Its Affinity for Capped mRNA

Abstract: In eukaryotes, a key step in the initiation of translation is the binding of the eukaryotic initiation factor 4E (eIF4E) to the cap structure of the mRNA. Subsequent recruitment of several components, including the small ribosomal subunit, is thought to allow migration of initiation complexes and recognition of the initiation codon. Mitogens and cytokines stimulate the phosphorylation of eIF4E at Ser 209 , but the functional consequences of this modification have remained a major unresolved question. Using flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
202
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(228 citation statements)
references
References 33 publications
21
202
5
Order By: Relevance
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussionmentioning
confidence: 99%
“…These data are quite surprising in light of previous reports where phosphorylation of Ser209 was most often correlated with cell growth in mammalian cells and was also shown to be critical for growth in Drosophila in toto (19). Although it was first reported that phosphorylation of eIF4E enhanced its affinity for the cap (25), reconstitution experiments of eIF4F complexes with purified molecules indicated that phosphorylation of eIF4E was not a prerequisite for complex formation with eIF4G (28), it was not required for translation (27), and it even reduced cap binding in vitro (43). Nevertheless, phosphorylation of Ser209 may still modulate a number of other protein-protein interactions that can affect the multiprotein 43S or 48S preinitiation complex, since the binding of eIF4E to eIF4G per se is known to change eIF4GI conformation, rendering it accessible to proteolytic cleavage (13,28).…”
Section: Discussionmentioning
confidence: 99%
“…This process is controlled by eIF4F, a complex composed of three core proteins: 1) eIF4E, which binds to the 7-methylguanosine cap on the 5′-end of mRNA, 2) eIF4A, which functions as an ATP-dependent RNA helicase, and 3) eIF4G, which contains binding sites for eIF4E and eIF4A, and functions as a molecular platform for assembling the eIF4F complex [27]. Affinity of eIF4F for the 7-methylguanosine cap can be modified by phosphorylation of eIF4E on Ser-209, which reduces its cap binding affinity as demonstrated in vitro [28]. Although the precise effects of eIF4E phosphorylation on translational efficiency of specific mRNAs have not been elucidated in cardiac muscle, we have shown in previous studies that eIF4E phosphorylation is increased in response to pressure overload hypertrophy [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…It has long been thought that phosphorylation increases the capbinding affinity of eIF4E. (49) Recent studies have now challenged this view (50,51) (discussed in Ref. 48).…”
Section: Introductionmentioning
confidence: 99%